Human neutrophil peptide-1 (HNP-1): a new anti-leishmanial drug candidate. - Sara Dabirian; Yasaman Taslimi; Farnaz Zahedifard; Elham Gholami; Fatemeh Doustdari; Mahdieh Motamedirad; Shohreh Khatami; Kayhan Azadmanesh; Susanne Nylen; Sima Rafati (Public Library of Science (PLoS), 2013)
The toxicity of available drugs for treatment of leishmaniasis, coupled with emerging drug resistance, make it urgent to find new therapies. Antimicrobial peptides (AMPs) have a strong broad-spectrum antimicrobial activity with distinctive modes of action and are considered as promising therapeutic agents. The defensins, members of the large family of AMPs, are immunomodulatory molecules and important components of innate immune system. Human neutrophil peptide-1 (HNP-1), which is produced by neutrophils, is one of the most potent defensins. In this study, we described anti-parasitic activity of recombinant HNP-1 (rHNP-1) against Leishmania major promastigotes and amastigotes. Furthermore, we evaluated the immunomodulatory effect of rHNP-1 on parasite-infected neutrophils and how neutrophil apoptosis was affected. Our result showed that neutrophils isolated from healthy individuals were significantly delayed in the onset of apoptosis following rHNP-1 treatment. Moreover, there was a noteworthy increase in dying cells in rHNP-1- and/or CpG-treated neutrophils in comparison with untreated cells. There is a considerable increase in TNF-α production from rHNP-1-treated neutrophils and decreased level of TGF-β concentration, a response that should potentiate the immune system against parasite invasion. In addition, by using real-time polymerase chain reaction (real-time PCR), we showed that in vitro infectivity of Leishmania into neutrophils is significantly reduced following rHNP-1 treatment compared to untreated cells.